Emotional mimicry in social context - Hess, Ursula 1960-; Fischer, Agneta 1958- (Studies in emotion and social interaction. Second series, 2016)
In everyday life we actively react to the emotion expressions of others, responding by showing matching, or sometimes contrasting, expressions. Emotional mimicry has important social functions such as signalling affiliative intent and fostering rapport and is considered one of the cornerstones of successful interactions. This book provides a multidisciplinary overview of research into emotional mimicry and empathy and explores when, how and why emotional mimicry occurs. Focusing on recent developments in the field, the chapters cover a variety of approaches and research questions, such as the role of literature in empathy and emotional mimicry, the most important brain areas involved in the mimicry of emotions, the effects of specific psychopathologies on mimicry, why smiling may be a special case in mimicry, whether we can also mimic vocal emotional expressions, individual differences in mimicry and the role of social contexts in mimicry.